LAPORAN KASUS: PANSITOPENIA BERAT AKIBAT EHRLICHIOSIS PADA ANJING LOKAL DISERTAI KOINFEKSI DEMODEKOSIS DAN DERMATOFITOSIS - MR, Jazuli Azra; Putriningsih, Putu Ayu Sisyawati; Erawan, I Gusti Made Krisna (VITEK : Bidang Kedokteran Hewan, 2025)
Ehrlichiosis is caused by bacteria of the genus Ehrlichia, which are transmitted by arthropod vectors, particularly the tick Rhipicephalus sanguineus. Mites of the genus Demodex cause demodicosis, which often occurs secondarily as a result of malnutrition or immunosuppressive conditions in dogs. Dermatophytosis in dogs can be caused by various fungal species, one of which is Microsporum sp., a zoonotic pathogen. This case report discusses a one-year-old local female dog with a combined infection of Ehrlichia canis, Microsporum sp., and Demodex sp. The dog exhibited clinical signs of pruritus, alopecia, skin lesions, and pale mucous membranes. Hematological examination indicated leukopenia, macrocytic hypochromic anemia, and thrombocytopenia. Serological testing revealed the presence of antibodies to Ehrlichia sp. Skin scraping and fungal culture confirmed a Demodex sp. infestation and a dermatophytosis infection caused by Microsporum sp. Treatment included intravenous fluids, doxycycline antibiotics, hematodin, and neurotropic agents. Although the patient initially showed clinical improvement, the condition worsened and ultimately resulted in death. This case emphasizes the importance of early diagnosis and comprehensive management of multi-etiological infections in dogs.